2023
DOI: 10.1002/uog.26226
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of screening and valacyclovir‐based treatment strategies for first‐trimester cytomegalovirus primary infection in pregnant women in France

Abstract: ObjectiveTo assess effectiveness, cost and cost‐effectiveness of four screening strategies for first‐trimester cytomegalovirus (CMV) primary infection (T1 PI) in pregnant women in France.MethodsWe compared four strategies of screening for CMV during pregnancy in France: no screening (S1), current screening in “real life” (25 to 50% pregnant women) (S2), universal screening (S3) and universal screening associated with valaciclovir in case of T1 PI (S4). Outcomes were total costs, effectiveness (number of congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, a recent French cost-effectiveness study showed that universal screening in conjunction with valaciclovir treatment would be cost-effective compare to current practice. 32 …”
Section: Evidence and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent French cost-effectiveness study showed that universal screening in conjunction with valaciclovir treatment would be cost-effective compare to current practice. 32 …”
Section: Evidence and Recommendationmentioning
confidence: 99%
“… 14 Discordant CMV IgG results are reported for 1.0–2.6% of samples, mainly those with IgG levels below twice the cut-off value of the test. 32 We recommend repeating weakly positive IgG results with a second assay or sending the sera to a reference laboratory. Sera that are positive with both assays can be declared positive; those with discordant results should be considered equivocal and declared negative.…”
Section: Evidence and Recommendationmentioning
confidence: 99%
“…There is no consensus in the global literature regarding the cost-effectiveness of hCMV screening in pregnant women [ 138 , 141 , 142 , 143 ]. However, as demonstrated by Périllaud-Dubois et al, universal hCMV screening combined with valacyclovir-based treatment, particularly when hCMV infection is detected in the first trimester of pregnancy, could be more cost-effective than currently accepted strategies for preventing cCMV and treating its complications [ 144 ]. An argument against the introduction of universal hCMV screening is the potential risk of increasing the rate of pregnancy termination in patients diagnosed with primary hCMV infection who may not have developed cCMV or its complications [ 145 ].…”
Section: Discussionmentioning
confidence: 99%